Water Level Control Monitoring Based On Arduino Uno R3 Atmega 238p Using Lm016l LCD at STMIK Hang Tuah Pekanbaru - Wahyuni, Refni; Sentana, Jeri Trio; Muhardi, Muhardi; Irawan, Yuda (Universitas Muhammadiyah Yogyakarta, 2021)
Water plays an important role in the survival of living creatures on earth. The advancement of computerized technology encourages people to make appropriate equipment that can be utilized in various aspects of life, such as ease in controlling the performance of water pumps in the shelter. STMIK Hang Tuah Pekanbaru uses system level switch but there are some weaknesses also in this system level switch that pump will live more than 1 time a day if there is damage to the buoy. In this study will be made a tool that can do the monitoring water height automatically.